Clostridium difficile suppresses colonic vasoactive intestinal peptide associated with altered motility - A. Nassif; W. E. Longo; R. Sexe; M. Stratton; J. Standeven; A. M. Vernava; D. L. Kaminski (Hindawi Limited, 1995)
We investigated whether Clostridium difficile toxin alters colonic tissue levels of vasoactive intestinal peptide (VIP) at the expense of changes in colonic motility in the isolated perfused rabbit left colon. Colonic inflammation was induced by the intracolonic administration of 10−8 M C. difflcile toxin. Strain gauge transducers were sewn onto the serosal surface of the colon to evaluate colonic motility. C. difflcile administration produced histologic changes consistent with epithelial damage. This was associated with an increased production of prostaglandin E2 and thromboxane B2. Tissue levels of VIP but not substance P were significantly reduced. This was associated with an increased number of contractions per minute and an average force of each colonic contraction. These results suggest that tissue levels of VIP are suppressed by C. difflcile and may participate in colonic dysmotility during active inflammation.